2008
DOI: 10.1002/jbm.a.32236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of esterified hyaluronan‐gelatin polymer composites suitable for chondrogenic differentiation of mesenchymal stem cells

Abstract: Composite scaffolds of homogeneously mixed esterified hyaluronan (HY) and gelatin (G) were manufactured with variable component compositions (HY100%; HY95%/G5%; HY70%/G30%). The goals of this study were to analyze the produced composite scaffolds using physical and chemical methods, e.g., scanning electron microscopy, IR-spectroscopy, water contact angle, protein assay, and tensile testing as well as to assess the effects of adding gelatin to the composite scaffolds on attachment, proliferation and chondrogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 67 publications
(163 reference statements)
3
36
1
Order By: Relevance
“…Gelatin-containing composite scaffolds exhibited stronger promotion of collagen type II than pure hyaluronan scaffolds. [65] Bian et al showed that functionalizing HA hydrogels with N-cadherin mimetic peptides can promote early chondrogenesis of human bone marrow-derived MSCs and cartilage-specific matrix production. [66] Nava et al Biomaterials for 3D Cell Biology Prospective Article fabricated 3D structural niches in an organic-inorganic photoresist (SZ2080) with 1% concentration of Irgacure 369 photoinitiator [2-benzyl-2-dimethylamino-1-(-4-morpholinophenyl)-butanone-1] via 2PP and investigated tuning the mechanical properties of the niches through coating with thin layers of biomimetic hyaluronan-and gelatin-based hydrogels.…”
Section: Synthetic Stem Cell Niches With Mesenchymal Stem Cells Diffementioning
confidence: 99%
“…Gelatin-containing composite scaffolds exhibited stronger promotion of collagen type II than pure hyaluronan scaffolds. [65] Bian et al showed that functionalizing HA hydrogels with N-cadherin mimetic peptides can promote early chondrogenesis of human bone marrow-derived MSCs and cartilage-specific matrix production. [66] Nava et al Biomaterials for 3D Cell Biology Prospective Article fabricated 3D structural niches in an organic-inorganic photoresist (SZ2080) with 1% concentration of Irgacure 369 photoinitiator [2-benzyl-2-dimethylamino-1-(-4-morpholinophenyl)-butanone-1] via 2PP and investigated tuning the mechanical properties of the niches through coating with thin layers of biomimetic hyaluronan-and gelatin-based hydrogels.…”
Section: Synthetic Stem Cell Niches With Mesenchymal Stem Cells Diffementioning
confidence: 99%
“…Human MSCs (hMSCs) are known to express multiple types of collagens and integrins (Docheva et al, 2007;Gronthos et al, 2001). Matrix and integrin-associated differentiation of hMSC towards chondrocytes and osteocytes have been reported (Kundu et al, 2008;Angele et al, 2008). However, their roles in cardiac differentiation of hMSCs are not well studied.…”
Section: Introductionmentioning
confidence: 98%
“…One is to improve the cell adhesion onto HA-based scaffolds by coating of scaffolds with ECM proteins such as collagen and fibronectin [19] or covalent binding of Arg-Gly-Asp (RGD) to a cross-linked HA [20]. The other one is to develop HA-based hybrid scaffolds in the form of nanofibers, hydrogels, and sponges by combining HA with other biomaterials such as collagen [1,21], gelatin [8,22,23], chitosan [24,25] and silk fibroin [18,26].…”
Section: Introductionmentioning
confidence: 99%